Production and characterization of cellulase-free xylanase from Trichoderma inhamatum - de Oliveira da Silva, Leonor Alves [UNESP]; Carmona, Eleonora Cano [UNESP] (Humana Press Inc, 2008)
The production of extracellular cellulase-free xylanase from Trichoderma inhamatum was evaluated in liquid Vogel medium with different carbon sources as natural substrates and agricultural or agro-industrial wastes. Optimal production of 244.02 U/mL was obtained with xylan as carbon source, pH 6.0 at 25 degrees C, 120 rpm, and 60-h time culture. Optimal conditions for enzyme activity were 50 degrees C and pH 5.5. Thermal stability of T. inhamatum xylanolytic complex expressed as T(1/2) was 2.2 h at 40 degrees C and 2 min at 50 degrees C. The pH stability was high from 4.0 to 11.0.These results indicate possible employment of such enzymatic complex in some industrial processes which require activity in acid pH, wide-ranging pH stability, and cellulase activity absence.
Keywords: xylanase; Trichoderma inhamatum; optimization; enzyme characterization; enzyme regulation